Evaluasi Pestisida Nabati dengan Ekstrak Mimba (Azadirachta sp.) untuk Pengendalian Pertumbuhan Antraknosa pada Buah Cabai - Paradisa, Yashanti Berlinda; Wahyuni; Mulyaningsih, Enung Sri; Perdani, Ambar Yuswi; Prianto, Arief Heru (Jurnal Fitopatologi Indonesia, 2021)
Evaluation of Plant-based Pesticide Containing Neem Extract (Azadirachta sp.) to Control Anthracnose Growth in Chili Fruits Chili pepper is one of the important horticultural commodities in Indonesia. Anthracnose is one of the major diseases causing yield losses up to 35% of the total production. This study was aimed to evaluate the efficacy of plant-based pesticides containing neem extract for controlling anthracnose growth in chili fruits. The research was conducted at the Research Center for Biotechnology, LIPI, from March until August 2019. Assays of in vitro and in vivo were arranged in a factorial randomized block design with four replications of each treatment. In vitro assay was performed by observing the growth of Colletotrichum acutatum and Colletotrichum gloeosporioides in culture media supplemented each with two pesticide formulations (Agr I and Agr II) in six concentrations of 0%, 0.5%, 1%, 2%. 3%, 4%, and 5%. In vivo assays were conducted by injecting spores of C. acutatum and C. gloeosporioides into fresh fruits of long-large-fruited chilies and long-curly-fruited chilies treated with Agr I at concentrations 0%, 5%, 10, and 15%. Results of in vitro assay showed that both Agr I and Agr II could inhibit both Colletotrichum growth and Agr I inhibited both fungal growth higher than Agr II. However, results of in vivo tests showed that Agr I could not inhibit both Colletotrichum in all chili fruits.